Assessment of geometric errors of Advanced Himawari-8 Imager (AHI) over one year operation. (June 2016) - Takeuchi, Wataru
Abstract: This paper presents an approach to check a geometric performance of Advanced Himawari-8 imager (AHI) and demonstrate and evaluate a new approach to ensure more geometric accurately focusing on visible imagery in 500 meters. A series of processing is supplemented by ground control points of shore lines, land mark locations and digital elevation model. Firstly, a template matching technique is conducted to find a best matching point by simply moving the center of AHI sub-image over each point in a reference image of shore lines and calculating the sum of products between the coefficients and the corresponding neighbourhood pixels in the area spanned by the filter mask. Secondly, ortho-rectification processing is carried out to compensate for the geodetical distortions with respect to the acquisition condition including viewing geometry and so on. As a result, an average of root mean square sum of residual errors with system correction and that of precise geometric correction are shown. Overall geometric accuracy is about 1 to 1.5 pixels from 2015 March to July and it also gradually decreased down to 0.2 to 0.8 from 2015 September to 2016 February. AHI is officially open to public for operational use as of July 1, 2015 and after that operation date geometric errors are reasonably satisfied within one pixels of errors.